2017
DOI: 10.1038/aps.2017.118
|View full text |Cite
|
Sign up to set email alerts
|

The ceramide pathway is involved in the survival, apoptosis and exosome functions of human multiple myeloma cells in vitro

Abstract: Multiple myeloma (MM) is characterized by the clonal proliferation of malignant plasma cells and refractoriness to traditional therapies. It has been shown that exosomes are involved in modulating the progression and the metastasis of cancers through microRNAs (miRs). Ceramide is a type of sphingolipid; the ceramide pathway of exosomal secretion has been shown to affect the apoptosis of cancer cells. But the role of this pathway in MM cell function, exosome function and miR regulation remains unknown. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 29 publications
11
63
0
Order By: Relevance
“…Particle size and concentration analysis. The analyses of size and concentration were in consistent with our previous studies [15,20] . In details, exosomes were resuspended in PBS, the particle size and concentration were measured by using the Nano Tracking System 300 (NTA300, Malvern Instruments, UK).…”
Section: Exosome Isolation Detection and Quanti Cationsupporting
confidence: 90%
See 2 more Smart Citations
“…Particle size and concentration analysis. The analyses of size and concentration were in consistent with our previous studies [15,20] . In details, exosomes were resuspended in PBS, the particle size and concentration were measured by using the Nano Tracking System 300 (NTA300, Malvern Instruments, UK).…”
Section: Exosome Isolation Detection and Quanti Cationsupporting
confidence: 90%
“…C6 ceramide (C6-cer) is a short-chain, cell-permeable analog of ceramide that has been utilized in preclinical studies to mimic the effects of endogenous ceramide [16] . We have previously showed that C6-cer treated MM exosomes could inhibit the proliferation of MM cells, indicating the antitumor role of C6-cer by exosomes [15] . However, whether C6-cer treated MM cell-derived exosomes could affect angiogenesis remains largely unknown.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As in A, before n-SMase action SM stabilizes membrane structure, while Cer production by n-SMase induces spontaneous negative curvature to the membrane of endosomes, thus promoting the formation of internal vesicles inside MVBs. Subsequent in vitro works reported that, while exogenous cell permeable C6 Cer dose-dependently increases the number of exosomes released from multiple myeloma cells (51), pharmacological or genetic block of n-SMase inhibited packaging of the prion protein into exosomes (52) and reduced exosome release among others in HEK cells (53), T cells (54), N2a cells (55), astrocytes (56), microglia (57), macrophages (58), hepatocytes (59), and multiple myeloma cells (51). Also, in vivo, in the brain and serum of 5XFAD mice, a transgenic model of Alzheimer's disease (AD), the n-SMase inhibitor, GW4869, decreased exosome concentration (60).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Apart from miRNAs and proteins, there are other exosome-associated treatment methods for MM [ Table 1]. For instance, C6 ceramide, an exogenous ceramide supplement, was found to dosedependently stimulate exosome secretion and elevate the exosome levels of some tumor-suppressive miRNAs, such as miRNA-202, miRNA-16, miRNA-29b, and miRNA-15a, thus increasing the apoptosis and inhibiting the proliferation of recipient MM cells, indicating that it is a target for MM treatment [32]. Exosomes also show anti-tumor immune effects.…”
Section: Other Exosome-associated Treatment Methods For MMmentioning
confidence: 99%